Analisis Quality Control Komponen Excavator (Tail Frame) pada PT. XYZ dengan Metode Six Sigma - Prihandoko, Danang; Aprilana, Andhira; Larasati, Firsty; Nabil, Nabil (STIE Ekuitas, 2020)
The purpose of this study is to determine the level of sigma that has been achieved by the company in producing tail frame, determine the causes of defects in tail frame products and provide improvements that can be done by companies to reduce defects in tail frame products using the Six Sigma method, namely DMAIC (Define, Measure, Analyze, Improve, Control). The research method is quantitative where the data used in the form of digital data relating to the production number of excavator components is the tail chassis and the amount of defective product data from the production of the tail chassis and the time horizon in this study was carried out cross-sectionally. Meanwhile, qualitative data in the form of written information on the type of defect production, the causes of defective products, the production flows and the raw materials used. The results achieved can be seen that the level of sigma in tail frame products is 4.38 in 2017 and 4.36 in 2018. It can be concluded that the company has not achieved the best industrial production quality, namely world class industry with a sigma level of 6. Keywords: Six Sigma; DMAIC; Quality Control